2000
DOI: 10.1070/rc2000v069n07abeh000540
|View full text |Cite
|
Sign up to set email alerts
|

The formation of carbon filaments upon decomposition of hydrocarbons catalysed by iron subgroup metals and their alloys

Abstract: The CP-conserving Minimal Supersymmetric Standard Model (MSSM) contains three neutral Higgs bosons [1 -5], the lighter and heavier CP-even scalars h and H, respectively, and the CP-odd pseudoscalar A. While the MSSM Higgs sector is CP-conserving at Born level even in the presence of CP-phases, loop effects mediated dominantly by third generation squarks can generate significant CP-violating scalar-pseudoscalar transitions, leading to mixing of the neutral Higgs states into the mass eigenstates H 1 , H 2 , H 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(51 citation statements)
references
References 103 publications
(78 reference statements)
6
35
0
3
Order By: Relevance
“…Despite the fact that the role of iron carbide in decomposition of hydrocarbons and CO disproportionation is widely discussed in the literature [14,19,33,[35][36][37][38], there is no clear answer to this question. The main problem is that it is impossible to carry out a comprehensive physicochemical study of working catalysts under in situ conditions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the fact that the role of iron carbide in decomposition of hydrocarbons and CO disproportionation is widely discussed in the literature [14,19,33,[35][36][37][38], there is no clear answer to this question. The main problem is that it is impossible to carry out a comprehensive physicochemical study of working catalysts under in situ conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Ni-Cu-Al 2 O 3 catalyst may serve as an example. It has been shown to have improved carbon capacity during methane decomposition and give CFC with different microstructural properties in comparison with Ni-Al 2 O 3 [12,19,21,22].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the last decades, it was reported that metal nanoparticles can undergo partial carburization, i.e., the chemical transformation of metal into metal carbide, and subsequent reverse decomposition during the synthesis of carbon filaments and nanotubes by the catalytic thermal decomposition of hydrocarbons. In 1970–1980s, the growth of carbon filaments on metallic iron catalyst was actively studied by Buyanov and Chesnokov, and a carbide cycle mechanism of the growth was proposed [70–75]. According to this mechanism, a metastable carbide-like intermediate compound was formed in the subsurface layer of a catalytic particle as a result of the decomposition of hydrocarbon.…”
Section: Reviewmentioning
confidence: 99%
“…The decomposition of intermediate carbide led to the supersaturation of metal by carbon. Indeed, the degradation of iron carbide Fe 3 C results in the mixture of carbon and iron with a carbon content of 6–7 wt %, whereas the saturated solid solution of carbon in iron contains not less than 0.025 wt % carbon [75]. Thus, a large carbon concentration gradient was created in the bulk of the catalytic particle.…”
Section: Reviewmentioning
confidence: 99%